Nonlinear analysis of the plasma wave decay - Khvesyuk, V.I.; Karbushev, D.N. (Вопросы атомной науки и техники, 2009)
Distortions of drift waves form connected with nonlinear processes agreed upon by influence of plasma shear flows on wave are considered. Plasma velocities are directed along line of wave propagation. It is shown that result of such an influence is strong transformation of wave. The overturn is achieved. It leads to wave decay.